Emergency Preparedness and Response Assessment : Bosnia and Herzegovina - World Bank (World Bank, Washington, DC, 2021)
The framework for ready2respond (R2R) was developed in reference to the role of the World Bank in disaster risk reduction. While strengthening emergency preparedness and response (EP and R) is a sound investment on its own, it also supports the World Bank Group’s broader risk reduction efforts and fundamental goal of eliminating poverty and promoting shared prosperity. This report includes the assessment of the EP and R capacities of Bosnia and Herzegovina based on the R2R diagnostic methodology, as designed by the World Bank and executed by prepared international (PPI). Data from the desk review and key informant interviews in country generated findings on all five core components of the diagnostic - legal and institutional frameworks, information, facilities, equipment, and personnel - which include 18 criteria, 72 indicators, and 360 attributes. In the diagnostic, these 360 attributes are scored with either 0 (not in place) or 1 (in place). The diagnostic identifies missing elements so that they can be acknowledged as capacity development needs and opportunities. This report provides a summary of the EP and R capacities per component, as assessed by PPI in the first half of 2020. The full assessment report, structured in accordance with the R2R methodology, can be found in annex 1. The report also makes key investment recommendations, which have been identified for the World Bank and other stakeholders to consider as they work to strengthen EP and R capacities in the country.